2013
DOI: 10.1038/ki.2013.220
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study measuring the prevalence of chronic kidney disease among adults in West Malaysia

Abstract: In this population-based study, we determine the prevalence of chronic kidney disease in West Malaysia in order to have accurate information for health-care planning. A sample of 876 individuals, representative of 15,147 respondents from the National Health and Morbidity Survey 2011, of the noninstitutionalized adult population (over 18 years old) in West Malaysia was studied. We measured the estimated glomerular filtration rate (eGFR) (CKD-EPI equation); albuminuria and stages of chronic kidney disease were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(83 citation statements)
references
References 16 publications
5
72
4
Order By: Relevance
“…Furthermore, CKD is also related to both a higher prevalence of cardiovascular disease and premature death [1], [2]. The estimated proportion of patients with CKD in the general population is approximately 10% in the United States, 7% in the United Kingdom, 9−10% in Asian countries and 19% in Japan [3][7]. The prevalence of CKD has been increasing significantly with time [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CKD is also related to both a higher prevalence of cardiovascular disease and premature death [1], [2]. The estimated proportion of patients with CKD in the general population is approximately 10% in the United States, 7% in the United Kingdom, 9−10% in Asian countries and 19% in Japan [3][7]. The prevalence of CKD has been increasing significantly with time [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors can influence albumin excretion, including obesity, age, sex, distant inflammation, high blood pressure, infection and drug use [29], resulting in wide fluctuations and hence false positivity of albuminuria. Several authors found a high percentage (>50%) of false-positive albuminuria at low values [urinary UACR 30–50 mg/g; dipstick proteinuria +], but less at higher values or dipstick  ++ and  +++ [11, 30, 31]. In the same way, CV I or repeatability of UACR is very high (>50%), and this variability is higher in low UACR ranges (>100%) [32].…”
mentioning
confidence: 99%
“…Many of them indicated that they would like to take part in the 2-day scenario in the first month if it was allowed. In another population-based study in West Malaysia, only 52.2% of respondents with albuminuria agreed to be retested in the following weeks [8]. This research was a sub-study of another large-scale cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the DAY-1 + DAY-2 strategy was excluded from the cost-effectiveness analysis due to the increased time costs associated with it. The gold standard (DAY-1 + MONTH-2 + MONTH-3) was eliminated from the cost-effectiveness analysis for the following reasons: 1) The study initially defined the gold standard for purposes of validity assessment of various strategies and was not concerned with its practicality [8]. Secondly, both the sensitivity and specificity of a gold standard should be 100%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation